PENGARUH MAKRO EKONOMI TERHADAP RETURN SAHAM PERBANKAN - Yenny Kornitasari; Muhammad Alfin Syaichul Farich (Contemporary Studies in Economic, Finance and Banking, 2024)
This study aims to see the effect of economic variables and world oil prices on banking stock returns. The method used in this study is a panel data regression analysis technique using quarterly data and the period from 2020 to 2022. The results of the research show that inflation and interest rates have a significant positive effect on banking stock returns, an increase in inflation causes people to reduce consumption and prefer to invest their money in the capital market, an increase in interest rates can result in an increase in income which has an impact on banking profits and performance, this is interesting investors' interest in investing in banking shares. Meanwhile, the exchange rate has a significant negative effect on banking stock returns, an increase or depreciation of the Rupiah exchange rate causes an increase in production costs and company expenses which can reduce company performance. so that investors become less interested in investing in the stock market. Meanwhile, world oil prices have no effect on banking stock returns